Magnetoresistansi Divais Spintronika TiO2:Co/Si/TiO2:Co [Spintronics Magnetoresistance Device with TiO2:Co/Si/TiO2:Co] - Edy Supriyanto; Agus Subagio; Hery Sutanto; Horasdia Saragih; Maman Budiman; Pepen Arifin; Sukirno Sukirno; Mohamad Barmawi (Institut Teknologi Bandung, 2007)
TiO2:Co thin films were grown on Si substrates by Metalorganic Chemical Vapor Deposition (MOCVD) technique using titanium(IV)isopropoxide and tris(2,2,6,6-tetramethyl-3,5-heptanedionato)cobalt (III), and oxygen gas. The films grown at temperature of 450 oC were crystalline having a rutile structure with (002) orientation. Based on Energy Dispersive Spectroscope (EDS) analysis, Co content in TiO2 was 1.83% and films exhibit ferromagnetic properties at room temperature. Hysteresis curves obtained from Vibrating Sample Magnetometer (VSM) measurement have coercive and saturation magnetic fields of 130 Oe and 2.1 emu/cm3, respectively. Application of TiO2:Co as injection material in spintronic device with TiO2:Co/Si/TiO2:Co structure was investigated. The effect of polarized spin injection (magnetoresistance phenomenon) was observed from the current-voltage characteristics of the device.